2004
DOI: 10.1042/cs20030246
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral cholinergic function in humans with chronic fatigue syndrome, Gulf War syndrome and with illness following organophosphate exposure

Abstract: In the present study, we have investigated whether the peripheral cholinergic abnormalities that we have reported previously [Spence, Khan and Belch (2000) Am. J. Med. 108, 736-739] in patients with chronic fatigue syndrome (CFS) are also present in those with Gulf War syndrome (GWS) and agricultural workers exposed to organophosphate pesticides, where cholinesterase inhibition is specifically implicated. We also looked at whether these abnormalities might be due to a reduction in the activity of cholinesteras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Autonomic effects are prominent in dynamic cerebral autoregulation, whereas vasomotor effects dominate static or steady‐state cerebral autoregulation. An impaired cerebral blood flow might be due to previously observed blood flow abnormalities in CFS, like prolonged acetylcholine‐induced vasodilatation in the microcirculation . In line with this, autonomic dysfunction may explain POTS and related cerebral blood flow impairment in CFS.…”
supporting
confidence: 55%
“…Autonomic effects are prominent in dynamic cerebral autoregulation, whereas vasomotor effects dominate static or steady‐state cerebral autoregulation. An impaired cerebral blood flow might be due to previously observed blood flow abnormalities in CFS, like prolonged acetylcholine‐induced vasodilatation in the microcirculation . In line with this, autonomic dysfunction may explain POTS and related cerebral blood flow impairment in CFS.…”
supporting
confidence: 55%
“…This is analogous to evidence in ill GWV, in which there are low-activity levels of PON and increased prevalence of low-activity variants of BChE [in ill GWV, the PON variant that is less effective may depend on the OP(s) to which the specific veteran was exposed]. Interestingly, GWV with chronic fatigue show a different bloodflow response to acetylcholine iontophoresis than do civilians with chronic fatigue syndrome, but they match the response of persons with chronic fatigue after OP exposure (49).…”
Section: Enzymes That Help Detoxify Acheis Differ In Ill Veterans Vsmentioning
confidence: 99%
“…In these patients, Khan et al (15) reported the response to ACh to be significantly higher and the time to decay to 50% peak to be ϳ40% longer than in healthy controls. They were, however, unable to demonstrate a similar phenomenon in patients with Gulf War Syndrome or in agricultural workers exposed to OP-containing pesticides (14).…”
Section: Discussionmentioning
confidence: 91%